Evaluation of Wireless LAN Quality of Service (QoS) in Primary Education Using TIPHON Standards - Oktaseli, Hizkiana Ruli; Slameto, Andika Agus (Politeknik Negeri Batam, 2025)
In the current digital era, internet connectivity in schools is crucial to support teaching and learning activities. SD Negeri 2 Sumber has implemented a wireless LAN network to provide internet access for students and teachers. This study aims to evaluate the network performance by measuring Quality of Service or QoS parameters, namely throughput, packet loss, delay, and jitter. The evaluation was conducted using Wireshark to monitor network traffic. The results show that the average throughput for video streaming is 4.251 Kbps, browsing is 1.425 Kbps, and downloading is 3.106 Kbps. The average packet loss is 1.66 % for video streaming, 4.6 % for browsing, and 2.66 % for downloading. The average delay for video streaming is 1.64 ms, browsing is 5.92 ms, and downloading is 2.32 ms. The average jitter is 1.62 ms for video streaming, 5.92 ms for browsing, and 2.16 ms for downloading. Based on the QoS parameters, the network quality is categorized as good according to TIPHON standards with a final score of 3.75. Although the overall network quality is good, there are several areas that need optimization, such as browsing activities, which show slightly higher throughput and jitter compared to other activities. This study provides a clear overview of wireless network performance and offers recommendations for further optimization to enhance user experience, particularly in activities involving browsing and school administration.